2015
DOI: 10.1039/c5cp00613a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular functionalization of silicene/Ag(111) by covalent bonds: a DFT study

Abstract: Among the 2D crystals, silicene, which forms sp(2)-sp(3) bonds, is expected to present a higher reactivity than graphene, characterized by sp(2) bonds only. However, silicene functionalization, in particular with organic molecules, remains an open question. By means of density functional theory, we study the adsorption of benzene, a model organic molecule, on (3 × 3) silicene on the (4 × 4) Ag(111) surface. Our calculations show that the dispersion interactions must be taken into account in order to describe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 70 publications
(168 reference statements)
0
8
0
Order By: Relevance
“…Kaloni et al, 48 showed that benzene and toluene molecules interacting with silicene physisorbed at the hollow site at an interacting distance of 3.41 and 3.35 Å with localized distortions within the silicene monolayer. On the other hand, adsorption of benzene onto silicene as reported by Stephan et al, 5 proceeds through a cycloaddition reaction, and benzene adopts a butterfly configuration mediated through the Si−C covalent bond. In our study, PZA prefers both parallel and perpendicular orientations, which could be due to the constituent O and N atoms of PZA governing the interaction resulting in the formation of strongly bound complexes onto silicene.…”
Section: Bioconjugated Complexesmentioning
confidence: 93%
See 1 more Smart Citation
“…Kaloni et al, 48 showed that benzene and toluene molecules interacting with silicene physisorbed at the hollow site at an interacting distance of 3.41 and 3.35 Å with localized distortions within the silicene monolayer. On the other hand, adsorption of benzene onto silicene as reported by Stephan et al, 5 proceeds through a cycloaddition reaction, and benzene adopts a butterfly configuration mediated through the Si−C covalent bond. In our study, PZA prefers both parallel and perpendicular orientations, which could be due to the constituent O and N atoms of PZA governing the interaction resulting in the formation of strongly bound complexes onto silicene.…”
Section: Bioconjugated Complexesmentioning
confidence: 93%
“…Silicene shares a honeycombed lattice similar to graphene, with high electron carrier mobility of 10 5 cm 2 V –1 s –1 . Silicene like graphene does not have a band gap at the Fermi level, and it has been reported that the spin–orbit coupling can induce a band gap within the clusters . However, unlike graphene analogues, silicene has a low buckled (puckered) conformation accounted from the mixed sp 2 –sp 3 hybridization, lack of π-electron delocalization, and strain induced due to mismatched hybridization. , In contrast to graphene and silicene, phosphorene is a direct band gap semiconductor with electron mobility of 1000 cm 2 V –1 s –1 , and its anisotropic electronic and optical properties originate due to the puckered honeycombed lattice. , What limits the large scale applicability of phosphorene is its facile nature to get oxidized readily on exposure to air which aids in degradation .…”
Section: Introductionmentioning
confidence: 99%
“…The electronic charge redistribution is counterbalanced by a change in elastic energy, for the overall germanene/Al(111) system, when switching from the 2T to the 1H germanene structure. Note that by using the optB86b-van der Waals density functional for the calculations, the 1H model also displays the same adsorption energy as the 2T one.…”
mentioning
confidence: 99%
“…We display the isosurfaces of the charge difference between isolated species (adsorbate molecules in gas phase and empty zeolites in vacuum, both without further relaxation) and the adsorbed phase (DClB molecules adsorbed within the zeolites), which allows depicting the local charge reorganization induced by the adsorption phenomenon. 57 Figures 2 and 3 present the charge-difference isosurfaces, respectively, for o-and m-DClB isomers adsorbed within the purely siliceous EMT-type zeolite (Figure 2) and its aluminosilicate form (Figure 3). To evidence both the substantial and the fine charge perturbations for each system, we used two isosurface values, namely, 0.004 and 0.002 e − /Å 3 for purely siliceous EMT-type zeolite and 0.02 and 0.009 e − /Å 3 for the aluminosilicate form.…”
Section: ■ Results and Discussionmentioning
confidence: 99%